MELAS: clinical features, muscle biopsy and molecular genetics MELAS: manifestações clínicas, biópsia muscular e estudo molecular - Paulo José Lorenzoni; Rosana H. Scola; Cláudia S. Kamoi Kay; Raquel C. Arndt; Aline A. Freund; Isac Bruck; Mara Lúcia S.F. Santos; Lineu C. Werneck (Arquivos de Neuro-Psiquiatria, 2009)
OBJECTIVE: The aim of the study was to analyze a series of Brazilian patients suffering from MELAS. METHOD: Ten patients with MELAS were studied with correlation between clinical findings, laboratorial data, electrophysiology, histochemical and molecular features. RESULTS: Blood lactate was increased in eight patients. Brain image studies revealed a stroke-like pattern in all patients. Muscle biopsy showed ralled-red fibers (RRF) in 90% of patients on modified Gomori-trichrome and in 100% on succinate dehydrogenase stains. Cytochrome c oxidase stain analysis indicated deficient activity in one patient and subsarcolemmal accumulation in seven patients. Strongly succinate dehydrogenase-reactive blood vessels (SSV) occurred in six patients. The molecular analysis of tRNA Leu(UUR) gene by PCR/RLFP and direct sequencing showed the A3243G mutation on mtDNA in 4 patients. CONCLUSION: The muscle biopsy often confirmed the MELAS diagnosis by presence of RRF and SSV. Molecular analysis of tRNA Leu(UUR) gene should not be the only diagnostic criteria for MELAS. OBJETIVO: O objetivo deste estudo foi analisar uma série de pacientes brasileiros portadores de MELAS. MÉTODO: Dez pacientes com MELAS foram estudados com correlação entre manifestações clínicas, alterações laboratoriais, estudo eletrofisiológico, histoquímico e molecular. RESULTADOS: O nível de lactato sérico estava aumentado em 8 pacientes. O estudo das imagens do crânio revelou padrão semelhante ao de AVC isquêmico em todos os pacientes. A biópsia muscular mostrou fibras rajadas vermelhas (RRF) em 90% dos pacientes na coloração pelo tricrômio de Gomori modificado e em 100% na reação histoquímica pela desidrogenase succicínica (SDH). A análise da coloração pela citocromo c oxidase indicou atividade deficiente em um paciente e acúmulo subsarcolemal em sete pacientes. Vasos com forte reação para SDH (SSV) ocorreram em seis pacientes. O estudo molecular do gene tRNA Leu(UUR) por PCR/RLFP e seqüenciamento direto mostrou a mutação A3243G no DNAmt de 4 pacientes. CONCLUSÃO: A biópsia muscular frequentemente confirma o diagnóstico de MELAS pela presença de RRF e SSV. O estudo molecular do gene tRNA Leu(UUR) não deve ser o único critério diagnóstico para MELAS.